The realisation of covering ‘aurat among the successful women in Malaysia - Naemah Hamzah; Adawiyah Ismail; Mohd Ismail Mustari; Bushrah Basiron (Universiti Kebangsaan Malaysia, 2014)
Among the conditions prescribed to working women is that they must perfectly cover themselves whenever they are at their working place. However, Muslims today are ‘haunted’ with a dilemma that influenced the thinking of whether to defend the Islamic laws or make changes to suit modernization. Thus, the involvement of women in the employment field to enhance the economic transformation clearly needs guidance and the right inspiration based on the Islamic law. Data were collected through qualitative design using in-depth interviews and analysis of documents involving past literatures and views of the contemporary scholars. In-depth interviews were conducted with women of higher grade in public sector, specifically grade 54 and JUSA. Supporting data of this study involved interviews with husbands, children, employers and colleagues to create a triangulation data. The findings of the study was analysed thematically using Nvivo 7.0 software.